Genetic evidence and new morphometric data as essential tools to identify the Patagonian seahorse Hippocampus patagonicus (Pisces, Syngnathidae) - González, Raul Alberto Candido (2014)
A genetic study to support morphometric analyses was used to improve the description and validate the Patagonian seahorse Hippocampus patagonicus (Syngnathidae) on the basis of a large number of specimens collected in the type locality (San Antonio Bay, Patagonia, Argentina). DNA sequence data (from the cytochrome b region of the mitochondrial genome) were used to differentiate this species from its relatives cited for the west Atlantic Ocean. Both phylogenetic and genetic distance analyses supported the hypothesis that H. patagonicus is a species clearly differentiated from others, in agreement with morphometric studies. Hippocampus patagonicus can be distinguished from Hippocampus erectus by the combination of the following morphometric characteristics: (1) in both sexes and all sizes of H. patagonicus, the snout length is always less than the postorbital length, whereas the snout length of H. erectus is not shorter than the postorbital length in the largest specimens; (2) in both sexes of H. patagonicus, the trunk length:total length (LTr:LT) is lower than in H. erectus (in female H. patagonicus: 0·27-0·39, H. erectus: 0·36-0·40 and in male H. patagonicus: 0·24-0·34, H. erectus: 0·33-0·43) and (3) in both sexes, tail length:total length (LTa:LT) in H. patagonicus is larger than in H. erectus (0·61-0·78 v. 0·54-0·64).